Safety and efficacy of anatomical tunneling technique for precise lung segment resection in complex anatomical settings - Kexin Cao; Jian Zhu; Jianan Zheng; Ke Wei; Zhihua Li; Zhijun Chen; Liang Chen; Weibing Wu (BMC Surgery)
Abstract Background Thoracoscopic segmentectomy is the main surgical method for the treatment of earlylung cancer. With the promotion of technology and increasingly accurate criteria for lung subsegments, lung nodules with complex positions involving intersegmental and multisegments have become technical bottlenecks. This study aimed to verify whether seeking anatomical conditions for creating a fissure by tunneling techniques with precise resection of lung segments could solve this bottleneck problem. Methods The clinical data of patients with lung nodules ≤ 2 cm located in the complex position in the Department of Thoracic Surgery of Jiangsu Provincial People's Hospital from January 2019 to August 2023 were collected. Date analyzed the characteristics of patients who underwent seeking anatomical conditions for creating a fissure by tunneling techniques with precise resection of lung segments (segment group) at complex setting and compared the surgical outcomes and complications between these lobectomy patients (lobectomy group) at similar locations. Results A total of 22 patients were included segment group and 47 patients were included lobectomy group. Except for the depth ratio or tumor size or consolidation tumor ratio (CTR), there were no significant differences in the other baseline data between the two groups. All patients in segment group received a satisfactory surgical margin. Compared to the lobectomy group, surgical outcomes were better in segment group (p < 0.05 for postoperative hospital stay and the counts of resected subsegments). Conclusion Seeking anatomical conditions for creating a fissure by tunneling techniques is a promising technique for performing precise resection of lung segments with a safe resection margin for patients with lung nodules at complex positions involving multiple segments. It can be used as a precise resection of lung segments technique.